The Investigation of Exact Solutions of Nonlinear Time-Fractional Klein-Gordon Equation by Using Generalized Kudryashov Method - Demiray, Seyma Tuluce; Pandir, Yusuf; Bulut, Hasan (Amer Inst Physics, 2014)
In this study, we consider exact solutions of nonlinear time-fractional Klein-Gordon equation by using generalized Kudryashov method (GKM). The nonlinear time-fractional Klein-Gordon equation can be converted into nonlinear ordinary differantial equation by transformation. Consequently, GKM has been implemented to find exact solutions of nonlinear time-fractional Klein-Gordon equation and we obtain some new solutions such as soliton solutions and hyperbolic function solutions. Moreover, we point out that this method is a generalized form of classical Kudryashov Method.
10th International Conference on Mathematical Problems in Engineering, Aerospace and Sciences (ICNPAA) -- JUL 15-18, 2014 -- Narvik Univ Coll, Narvik, NORWAY
Keywords: Nonlinear Time-Fractional Klein-Gordon Equation; Generalized Kudryashov Method; Soliton Solutions; Hyperbolic Function Solutions